2012
DOI: 10.1111/j.1750-3841.2012.02934.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quercetin Pharmacokinetics Following Oral Supplementation in Humans

Abstract: The current study describes for the first time, comprehensive evaluation of quercetin PK in humans from quercetin fortified oral food products at doses commonly used for quercetin supplementation. Owing to quercetin's potent antioxidant and anti-inflammatory actions, quercetin is widely being used as a nutritional supplement. In order to maximize the bioavailability of quercetin for its use in efficacy studies, it is important to determine its ideal oral carrier system and route for its delivery. The current r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…For example, quercetin AUC 0-24 h in adults was 8.9-89.1 μM · h following ingestion of onion-derived quercetin glucosides at a dose equivalent to 100 mg quercetin aglycone [51]. Quercetin C max was 0.29-2.26 μM in participants who ingested a beverage containing 500 mg quercetin aglycone [13]. Separate studies showed that intersubject variations for time to C max (T max ) and elimination half-life (t 1/2 ) of quercetin in adults were 69% and 122%, respectively, following ingestion of 100 mg apple-derived quercetin glycosides [63].…”
Section: Quercetin Bioavailability Varies Widely Between Individualsmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, quercetin AUC 0-24 h in adults was 8.9-89.1 μM · h following ingestion of onion-derived quercetin glucosides at a dose equivalent to 100 mg quercetin aglycone [51]. Quercetin C max was 0.29-2.26 μM in participants who ingested a beverage containing 500 mg quercetin aglycone [13]. Separate studies showed that intersubject variations for time to C max (T max ) and elimination half-life (t 1/2 ) of quercetin in adults were 69% and 122%, respectively, following ingestion of 100 mg apple-derived quercetin glycosides [63].…”
Section: Quercetin Bioavailability Varies Widely Between Individualsmentioning
confidence: 98%
“…In addition, the high intersubject differences in quercetin bioavailability may contribute to the inconsistent findings of clinical studies examining its cardioprotective activities. Indeed, quercetin bioavailability varies by 27% even when participants ingest quercetin in a standardized manner [13]. Thus, not only would quercetin absorption be variable, but also its cardioprotective activities may be diminished as a result.…”
Section: Implications For Quercetin-dependent Cardioprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The explanation for these discrepancies remains unclear, but the bioactivities of quercetin are related to its bioavailability. Unfortunately, marked interindividual variability exists in humans for the bioavailability of quercetin and other polyphenols [4][5][6]. For example, the coefficient of variation (CV) for plasma maximum concentrations (C max ) of quercetin (CV ¼ 61-92%) as well as that of anthocyanins and catechins (CV ¼ 18-177%) vary greatly between individuals after their oral ingestion [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological reports have demonstrated that quercetin has pronounced pharmaceutical effects, including anti-inflammatory, antioxidant, and antiviral activity. 25 In addition, quercetin is included in a novel class of chemotherapeutic drugs for the treatment of various cancers 26 and can also be combined with ultrasonic pretreatment to increase the concentration of quercetin to inhibit the growth of the prostate and skin cancer cell lines. 27 However, quercetin has low aqueous solubility, poor absorption, and rapid metabolism (bioavailability approximately 1%-5%), 28 all of which can generate in vivo results that differ from the powerful in vitro efficacy of quercetin.…”
Section: Introductionmentioning
confidence: 99%